Conflicting judgments and weakness of will - Heinzelmann, Nora (Philosophia, 2021)
This paper shows that our popular account of weakness of will is inconsistent with dilemmas. In dilemmas, agents judge that they ought to do one thing, that they ought to do something else, and that they cannot do both. They must act against either of their two judgments. But such action is commonly understood as weakness of will. An agent is weak-willed in doing something if she judges that she ought to and could do something else instead. Thus, it seems that, in a dilemma, the agent is weak-willed by definition. But this is puzzling: clearly, the two are different phenomena. The puzzle may support scepticism about weakness of will or dilemmas. Here, I argue that the two are consistent on a revised understanding of weakness of will. To do so, I further distinguish the mental states of an agent in a dilemma from those of a weak-willed person.
Online veröffentlicht: 25 August 2020
Gesehen am 27.01.2025